The (Unexpected) Structure of ?Rents? on the French and British Labour Markets - Andrew E. Clark; Claudia Senik (Institute for the Study of Labor (IZA), 2004)
This paper considers the allocation of labour on the French and British markets, using objective wage and subjective satisfaction data. We show that, in some sectors, workers enjoy both higher wages and higher job satisfaction. We argue that this reflects labour market wage rents. Perhaps surprisingly, wage rents are typical of the British public sector and permanent contracts, but not of their French counterparts. In France, such rents are found in full-time, rather than part-time jobs. Hence, the data provide little support for the usual a priori that the French labour market is structured along insider-outsider model lines, whereby wage rents are captured by the insiders of the public sector to the detriment of the private sector. However, they do suggest that part-time employment is involuntary to a far greater extent in France than in Great Britain.
Keywords: J41; J31; J28; C30; M51; 330; job satisfaction; wages; self-employment; public sector; permanent; full-time; rents; Lohnstruktur; Arbeitszufriedenheit; Rententheorie; Öffentlicher Dienst; Teilzeitarbeit; Vergleich; Schätzung; Grossbritannien; Frankreich